Quantitative Ultrasonographic Analysis of Changes of the Suprascapular Nerve in the Aging Population With Shoulder Pain - Wu, Wei-Ting; Chen, Lan-Rong; Chang, Hsiang-Chi; Chang, Ke-Vin; Özçakar, Levent (Frontiers in Bioengineering and Biotechnology, 2021)
Background Older people are vulnerable to painful shoulder syndromes, the majority of which are derived from degenerative rotator cuff pathologies. The suprascapular nerve (SSN) is closely related to the rotator cuff complex, and its role in shoulder pain has recently been highlighted. This study aimed to explore the differences in SSN among older people with and without shoulder pain, and to investigate the potential factors influencing the nerve size using ultrasound (US) imaging. Methods Participants aged ≥ 60 years were enrolled in the study. A systematic and bilateral US examination of the rotator cuff tendons was performed. The SSN was examined from its origin in the brachial plexus to the spinoglenoid notch of the infraspinatus fossa. The association between the nerve’s cross-sectional area (CSA) and rotator cuff lesions was analyzed using the generalized estimation equation. Results Among the 94 participants, 45 (with bilaterally asymptomatic shoulders) were classified into the control group, whereas 49 (with at least one-sided shoulder pain) were classified into the group with shoulder pain. The average CSAs of the SSN at the level of the brachial plexus, supraspinatus fossa, and infraspinatus fossa were comparable between the patients in the control group and those with shoulder pain. There was a higher prevalence of rotator cuff lesions and enlarged distal SSNs in the painful shoulders than in the asymptomatic shoulders of patients with unilateral involvement. A full-thickness tear of the supraspinatus tendon was associated with swelling of the SSN in the supraspinatus fossa (β coefficient = 4.068 mm2, p < 0.001). Conclusions In the older population, full-thickness tears of the supraspinatus tendon are independently associated with enlargement of the distal SSN. In cases with large rotator cuff tendon tears with poor response to conservative treatments, possible SSN entrapment should be considered and managed accordingly.